Fungemia due to Kodamaea ohmeri in a young infant and review of the literature (2016)
ABSTRACT: Fungal infections have become an important cause of morbidity and mortality in hospitalized children due to many complicating and underlying conditions. We present the case of a newborn infant with fungemia due to Kodamaea ohmeri who had a good outcome of the infection after using the combination of antifungal treatment and central venous catheter removal.